On the taxonomy and phylogeny of Ctenodrilus (Annelida: Cirratulidae) with a first report from South Africa - Weidhase, Michael; Bleidorn, Christoph; Simon, Carol A. (Marine Biodiversity, 2016)
The Ctenodrilidae is a species-poor family of the Annelida with an often debated affiliation, ranging from constituting a distinct annelid order to being part of the Cirratulidae. Furthermore, relationships of the included genera and species are not resolved. Ctenodrilus serratus, by far the most common member of this taxon, appears to have a worldwide distribution. As molecular data are lacking for most reports, it is unknown if this species is cosmopolitan, or a complex of potentially cryptic species. Here we describe the first discovery of C. cf. serratus from Kleinzee oyster farms (South Africa). Besides morphological characterization, we analyzed the CO1 sequence in comparison to C. serratus from Helgoland (Germany, North Sea). Additionally, we included several cirratulid sequences with a special focus on Dodecaceria and another ctenodrilid, Raricirrus beryli, to illuminate the relationship of C. serratus and the Ctenodrilidae in general. Our findings support the idea that both investigated ctenodrilids represent progenetic members of the Cirratulidae but do not support monophyly of the former Ctenodrilidae. Whereas C. serratus is closely related to Dodecaceria (or possibly nested within), R. beryli is recovered as a sister taxon to the multi-tentaculated cirratulid genera Cirratulus, Cirriformia and Timarete. Finally, the similarity of C. serratus to larvae of D. concharum is discussed, supporting the hypothesis of progenetic evolution.
World Polychaeta Database (WPolyDb). online June 2015, validly published March 2016